Cultivating a Global Identity - Joseph de Rivera; Harry A. Carson (Journal of Social and Political Psychology, 2015)
Increasing economic globalization creates conflicts that can only be constructively managed if individuals and groups realize they now belong to a single people. The required sense of such a community does not involve a social group identity—as though being human consisted of being categorized as a member of a superordinate group. Rather, it involves the realization that personal identity depends on the socio-emotional relations involved in community and that the current situation requires a community that is global rather than local or national. The nature of this personal global identity and the sort of global community that is needed is explored in this article. Developing a sense of unity amongst people has always required ritual celebration, and achieving the consciousness that persons worldwide now form a global community will require a particular type of ritual whose nature is described. The authors report on some pilot studies which demonstrate that it is possible to present the idea of global identity in a way that emphasizes personal active relationships rather than group belonging, that this may increase a sense of global identification, and that one can create a celebration that may enhance the sense of personal identity in a global community. We conclude by exploring the ways in which conceiving personal identity in communal terms has implications for research on global identity and conflict. And, finally, we report on present day initiatives that may develop a global communal consciousness, and identify and describe celebrations of community that may advance a sense of global community.